2022
DOI: 10.2196/39718
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mobile App for Self-Care Against COVID-19 Using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) Model: Methodological Study

Abstract: Background Mobile apps have been shown to play an important role in the management, care, and prevention of infectious diseases. Thus, skills for self-care—one of the most effective ways to prevent illness—can be improved through mobile health apps. Objective This study aimed to design, develop, and evaluate an educational mobile-based self-care app in order to help the self-prevention of COVID-19 in underdeveloped countries. We intended the app to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In order to design our app user interface to better communicate with patients, we sought out experts in user experience and software in these fields. This method of designing an app's user interface and user experience flow has been used in a number of studies [40,41]. It is important to note that a good user interface design is very important to a mobile app's acceptance by its users [42].…”
Section: Discussionmentioning
confidence: 99%
“…In order to design our app user interface to better communicate with patients, we sought out experts in user experience and software in these fields. This method of designing an app's user interface and user experience flow has been used in a number of studies [40,41]. It is important to note that a good user interface design is very important to a mobile app's acceptance by its users [42].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in addition to con rming it, we found the simple and user-friendly design of technologies as a positive factor. It should be noted that the design of the appropriate user interface makes the users more persuasive and this issue makes it easier for the patient to accept the designed system (10,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The use of health information technology systems can help patients with chronic diseases improve their quality of life by increasing their awareness of the diseases they have (7)(8)(9). Indeed, raising awareness and providing continuous education can help treat these patients more effectively (10)(11)(12). In the meantime, health information technologies can play an important role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the ADDIE model was used for the development of the mobile app, as it encompasses thorough editing phases and provides repeated correction opportunities during the training material design process. Additionally, the ADDIE approach is effective in organizing health practices and patient follow-up [ 25 , 26 ]. The ADDIE model is a well-established methodology for information transfer in adult education, and it has been widely utilized for the production of multimedia learning content [ 27 ].…”
Section: Introductionmentioning
confidence: 99%